2009
DOI: 10.1021/ef800779k
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Calcination/Carbonation Cycling and Thermal Pretreatment for CO2 Capture by Limestone and Dolomite

Abstract: Capturing carbon dioxide is vital for the future of climate-friendly combustion, gasification, and steam-reforming processes. Dry processes utilizing simple sorbents have great potential in this regard. Long-term calcination/carbonation cycling was carried out in an atmospheric-pressure thermogravimetric reactor. Although dolomite gave better capture than limestone for a limited number of cycles, the advantage declined over many cycles. Under some circumstances, decreasing the carbonation temperature increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 12 publications
8
118
1
Order By: Relevance
“…Eventually, multicyclic conversion of pretreated sorbents would converge towards a residual value for very large N as seen in experimental data [22]. In this limit, Eq.…”
Section: Models On Multicyclic Cao Conversionmentioning
confidence: 77%
See 3 more Smart Citations
“…Eventually, multicyclic conversion of pretreated sorbents would converge towards a residual value for very large N as seen in experimental data [22]. In this limit, Eq.…”
Section: Models On Multicyclic Cao Conversionmentioning
confidence: 77%
“…Yet, the model cannot explain the evolution of conversion found in some cases of activated sorbents [24]. For example, Chen et al [22] have shown that a natural limestone and a dolomite showed a residual conversion after 1000 carbonation/calcination cycles that actually depended on the details of thermal pretreatment even though identical looping conditions are used. Furthermore, depending on the relative values of X 0 and k D , the model predicts either a continuous increase or a decrease of conversion from X 0 up to reaching a residual value for large N .…”
Section: Models On Multicyclic Cao Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, very different results are obtained for deactivation rates when calcination is conducted under mild vs. severe conditions (Grasa and Abanades, 2006;Manovic and Anthony, 2008b;Manovic and Anthony, 2008d;Manovic et al, 2009;Wang et al, 2010) and also due to increases in carbonation temperature (Manovic and Anthony, 2008d) (both of which are reported to be due to the effect of sintering, see: Section 2.1 above). Longer carbonation times can regenerate the sorbent (Barker, 1973, Lysikov et al, 2007Chen et al, 2009) though the effect of this is somewhat inconsistent elsewhere (Manovic and Anthony, 2008d). A higher CO 2 concentration during carbonation has been shown to improve the uptake of some synthetic sorbents (Pacciani et al, 2008b).…”
Section: Sorbent Performancementioning
confidence: 99%